2002
DOI: 10.1002/ajim.10096
|View full text |Cite
|
Sign up to set email alerts
|

Association between bone lead concentration and blood pressure among young adults

Abstract: These results suggest that substantial lead exposure during childhood can increase BP during young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…A number of studies suggest an association between blood/bone lead and small increases in blood pressure (Cheng et al, 2001;Gerr et al, 2002;Hu et al, 1996;Korrick et al, 1999;Rothenberg et al, 2002;Nawrot et al, 2002;Schwartz 1995;Staessen et al, 1994). Lead also affects kidney function; decreased glomerular filtration rate was observed consistently in populations with mean PbB levels <20 μg/dl, and two studies reported effects at PbB <10 μg/dl (Kim et al, 1996;Muntner et al, 2003).…”
Section: Body Burdens Versus Exposures and Health Guidance Values 403mentioning
confidence: 93%
“…A number of studies suggest an association between blood/bone lead and small increases in blood pressure (Cheng et al, 2001;Gerr et al, 2002;Hu et al, 1996;Korrick et al, 1999;Rothenberg et al, 2002;Nawrot et al, 2002;Schwartz 1995;Staessen et al, 1994). Lead also affects kidney function; decreased glomerular filtration rate was observed consistently in populations with mean PbB levels <20 μg/dl, and two studies reported effects at PbB <10 μg/dl (Kim et al, 1996;Muntner et al, 2003).…”
Section: Body Burdens Versus Exposures and Health Guidance Values 403mentioning
confidence: 93%
“…Kidney function, evaluated by measurements of creatinine clearance rate was significantly higher in subjects with plumbism than in controls, but serum creatinine was not significantly different than in controls subjects. The results from these two studies (Gerr et al 2002;Hu 1991a) suggest the possibility that high childhood exposures to lead may contribute to higher blood pressure in adulthood. However, epidemiological studies of children have not found significant associations between increasing PbB and blood pressure (Factor-Litvak et al 1996;Friedlander 1981;Rogan et al 1978;Selbst et al 1993).…”
Section: Health Effectsmentioning
confidence: 99%
“…These studies suggest that bone lead levels may be predictors of certain health outcomes, including neurodevelopmental and behavioral outcomes in children and adolescents (Campbell et al 2000a;Needleman et al 1996Needleman et al , 2002Payton et al 1998); and hypertension and declines in renal function in adults Gerr et al 2002;Hu et al 1996aHu et al , 1998Korrick et al 1999;Rothenberg et al 2002a;Tsaih et al 2004). …”
Section: Bone and Tooth Lead Measurements The Development Of Noninvamentioning
confidence: 99%
See 2 more Smart Citations